Quick method for isolating RNA from raw and ripe fleshy fruits as well as for co-isolating DNA and RNA from polysaccharide- and polyphenol-rich leaf tissues - Pandit, Sagar Subhash; Mitra, Sirsha Sribas; Giri, Ashok P.; Gupta, Vidya Shrikant (Journal of Plant Biology, 2007)
Qualitative and quantitative changes in its chemical composition make it difficult to use any single procedure for isolating good-quality RNA from fruits at various ripening stages. Although the CTAB method has eliminated some specific problems, e.g., low pH in raw fruit or high levels of polysaccharides, oligosaccharides and phenolics in raw and ripe fruits, the total time required is long and unsuitable for high throughput. Here, we successfully modified this CTAB protocol to isolate good-quality RNA from (i) fleshy fruits, especially raw and ripe mangos; (ii) the leaves of a succulent air plant; and (iii) an oligosaccharide-rich onion epidermis. This RNA proved useful for downstream transcriptomic applications, where RT-PCR followed by RACE yielded the complete open reading frame of the (mango) terpene synthase gene. We also extended the utility of this protocol to co-isolate good-quality genomic DNA from the supernatant that remained after RNA precipitation. This preparation was useful for the arbitrary primer multilocus amplification of genomic DNA as well as for single locus diversity marker amplifications of the ctDNA and mtDNA.
Keywords: DNA-RNA co-isolation; fleshy fruit; Mango; oligosaccharide-rich; Ripening; transcriptomic studies